Development and evaluation of a mobile platform for teaching mathematics of CAD subjects. Issue 2 (4th March 2018) - Tang, Y.M.; Yu, K.M.
ABSTRACT: Nowadays, Hong Kong has adopted a new 3-3-4 academic structure for senior secondary education and higher education since 2012. Students can admit to most of the university programme without compulsory subject requirement. It means that students can admit to a programme without sufficient background on the underpinning subjects. Recently, it was found that a number of students were admitted to the engineering programmes without sufficient mathematical background, and it is a great challenge for the students study future engineering subjects, especially for the computer-aided product design (CAD) and other subjects that requires demanding mathematical background knowledge. In this project, a mobile learning platform is developed intend to provide a convenient and attractive channel for students to review and study the mathematics concepts and equations that need to be used in class. The platform encourages students' self-learning and facilitating them to learn other engineering subjects easily. Two tests were conducted to access students' mathematical performance before and after studying using the provided teaching materials. Students were divided into two groups studying with the mobile learning platform and traditional teaching notes. Experimental results show that the performance of the students on engineering mathematics were improved significantly by using the developed mobile learning platform. GRAPHICAL ABSTRACT: